Autism spectrum disorder - Goldy-Brown, Sarah (New York Lucent Press, 2018)
Not all autistic people are alike. One person living with autism spectrum disorder may not speak, while another may enjoy talking to friends and family. Educating readers about the facts concerning autism is important, as much misinformation is spread through the media. Readers discover the science behind this disorder and the ways it is diagnosed and treated today. Detailed infographics offer statistics at a glance, and a list of organizations to contact provides resources for people living with autism spectrum disorder, as well as their family and friends. Detailed Table of Contents, Full-Color Photographs, Further Information Section, Glossary, Index, Infographics, Sidebars, Websites.
"Portions of this book originally appeared in Autism by Toney Allman."
Includes bibliographical references (pages 86-90) and index.
13 - 17 years
105793
Keywords: Autism spectrum disorders